Selected Soybean Varieties Regulate Hepatic LDL-Cholesterol Homeostasis Depending on Their Glycinin:β-Conglycinin Ratio - Miguel Rebollo-Hernanz; Neal A. Bringe; Elvira Gonzalez de Mejia (MDPI AG, 2022)
Clinical studies indicate that the consumption of soybean protein might reduce cholesterol and LDL levels preventing the development of atherosclerotic cardiovascular diseases. However, soybean variety can influence soybean protein profile and therefore affect soybean protein health-promoting properties. This study investigated the composition and effects of nineteen soybean varieties digested under simulated gastrointestinal conditions on hepatic cholesterol metabolism and LDL oxidation in vitro. Soybean varieties exhibited a differential protein hydrolysis during gastrointestinal digestion. Soybean varieties could be classified according to their composition (high/low glycinin:β-conglycinin ratio) and capacity to inhibit HMGCR (IC50 from 59 to 229 µg protein mL−1). According to multivariate analyses, five soybean varieties were selected. These soybean varieties produced different peptide profiles and differently reduced cholesterol concentration (43-55%) by inhibiting HMGCR in fatty-acid-stimulated HepG2 hepatocytes. Selected digested soybean varieties inhibited cholesterol esterification, triglyceride production, VLDL secretion, and LDL recycling by reducing ANGPTL3 and PCSK9 and synchronously increasing LDLR expression. In addition, selected soybean varieties hindered LDL oxidation, reducing the formation of lipid peroxidation early (conjugated dienes) and end products (malondialdehyde and 4-hydroxynonenal). The changes in HMGCR expression, cholesterol esterification, triglyceride accumulation, ANGPTL3 release, and malondialdehyde formation during LDL oxidation were significantly (p < 0.05) correlated with the glycinin:β-conglycinin ratio. Soybean varieties with lower glycinin:β-conglycinin exhibited a better potential in regulating cholesterol and LDL homeostasis in vitro. Consumption of soybean flour with a greater proportion of β-conglycinin may, consequently, improve the potential of the food ingredient to maintain healthy liver cholesterol homeostasis and cardiovascular function.